1977
DOI: 10.3382/ps.0561373
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Low Dietary Salt on Egg Productioni , ,

Abstract: Diets calculated to be deficient in dietary salt were fed in a controlled experiment to individually caged chickens in egg production to evaluate the susceptibility of laying hens to less than the National Research Council's (N.R.C.) recommended level, 0.370% salt.The response of 600 laying hens was evaluated on either the control diet, which had 0.500% dietary salt added, or for one of these assumed to be deficient. These diets had either 0.250%, 0.125% or 0.000% dietary salt added to practical diets.Signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0

Year Published

1981
1981
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…Dilworth and Day (1976) reported a moderate to severe molt in hens fed a corn-soy diet without added salt for 14 to 28 days. Monsi and Enos (1977) also reported a heavy molt among hens during the third week when fed a no-salt-added diet. However, Whitehead and Shannon (1974), Nesbeth et al (1976b), and Begin and Johnson (1976) reported little or no molt among hens fed a diet with no added salt.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…Dilworth and Day (1976) reported a moderate to severe molt in hens fed a corn-soy diet without added salt for 14 to 28 days. Monsi and Enos (1977) also reported a heavy molt among hens during the third week when fed a no-salt-added diet. However, Whitehead and Shannon (1974), Nesbeth et al (1976b), and Begin and Johnson (1976) reported little or no molt among hens fed a diet with no added salt.…”
Section: Resultsmentioning
confidence: 90%
“…In recent years, a number of reports have been published on the response of laying hens to a low-sodium diet (Whitehead and Shannon, 1974;Nesbeth et al, 1976aNesbeth et al, ., 1976bMonsi and Enos, 1977). The major effect in most cases has been a sharp drop in egg production to near zero levels that is clearly reversible with the addition of sodium to the diet.…”
Section: Introductionmentioning
confidence: 95%
“…In the hen, cessation of ovulation occurs following starvation (Morris and Nalbandov, 1961) or chronic feeding of calcium deficient diets (Taylor et al, 1962;Gilbert and Blair, 1975;Luck and Scanes, 1979) or low sodium diets (Monsi and Enos, 1977). The young male chicken responds to fasting with reduced plasma levels of LH and FSH (Scanes et al, 1 Department of Nutrition.…”
Section: Introductionmentioning
confidence: 97%
“…Dilworth et al (1972a) reported that feed consumption, egg production and egg size were decreased with dietary salt levels of 0% to 0.25%. Monsi and Enos (1972) fed diets containing 0%, 0.125%, 0.25% and 0.5% added salt to laying hens and found that salt levels had no significant effect on egg weight, 1. Florida Agr.…”
Section: Introductionmentioning
confidence: 98%